Construction of a new technique in Aitken extrapolation method for solving Fredholm integral equation of the first kind with iterated kernel. - Aml Mohammed; Junaid Mustafa (College of Education for Pure Sciences, 2008)
Abstract In this paper a new technique for Aitken extrapolation method is used to solve F.I.E. k. This method requires many reiterative steps. Therefore, it depends on the iterative method which results in an increase in the rate of approximation of the solution and simultaneously it minimizes the number of the steps in comparison with the outdated successive method and iterative method itself.